Integrasi Keadilan Kontraktual Dan Perlindungan Data Pribadi Dalam Perjanjian Perjanjian Fintech Peer To Peer Lending - Azwar Fariz Aldaufa; Muhammad Ainun Naza (El-Dusturie, 2025)
Abstract: The development of peer-to-peer lending (P2PL) financial technology has facilitated access to financing in Indonesia, but on the other hand, it has raised legal issues, particularly regarding contractual fairness and personal data protection. P2PL contracts are generally drafted in the form of take-it-or-leave-it standard clauses, placing borrowers in a weak bargaining position and potentially creating an imbalance of rights and obligations between the parties. Furthermore, the misuse of personal data by operators or third parties, such as intimidation, dissemination of information, and use of data without clear consent, demonstrates the weakness of data protection mechanisms in the fintech ecosystem. This study aims to analyze the application of contractual justice principles in P2PL agreements, examine the effectiveness of personal data protection regulations in P2PL, and explore the relationship between contractual justice and personal data rights in digital contracts. The method used is normative legal research through the examination of legislation and related literature. The results of the study show that the application of contractual justice in P2PL has not been substantially implemented due to the dominance of the organizer in drafting clauses. Meanwhile, personal data protection, despite having a normative basis, has not been effective due to weak supervision and recovery mechanisms. Therefore, it is necessary to reformulate digital contracts that integrate transparency, risk proportionality, and user control over data in order to create a fair and ethical P2PL ecosystem.   Keyword: fintech; contractual justice; personal data, P2P lending; digital contracts.   Abstrak: Perkembangan teknologi finansial berbasis peer to peer lending (P2PL) mempermudah pembiayaan di Indonesia, namun di sisi lain menimbulkan problematika hukum, khususnya terkait keadilan kontraktual dan perlindungan data pribadi. Kontrak P2PL umumnya disusun dalam bentuk klausula baku yang bersifat take it or leave it, sehingga menempatkan peminjam pada posisi tawar yang lemah dan berpotensi menciptakan ketidakseimbangan hak serta kewajiban antara para pihak. Selain itu, praktik penyalahgunaan data pribadi oleh penyelenggara ataupun pihak ketiga, seperti intimidasi, penyebaran informasi, dan penggunaan data tanpa persetujuan yang jelas, menunjukkan lemahnya mekanisme perlindungan data dalam ekosistem fintech. Penelitian ini menganalisis penerapan prinsip keadilan kontraktual dalam perjanjian P2PL, mengkaji pengaturan perlindungan data pribadi dalam P2PL, serta menelaah hubungan antara keadilan kontraktual dan hak atas data pribadi dalam kontrak digital. Penelitian ini menggunakan pendekatan yuridis normatif melalui penelaahan peraturan-peraturan dan literatur yang relevan. Hasil penelitian menunjukkan penerapan keadilan kontraktual dalam P2PL belum terlaksana secara substansial karena dominasi penyelenggara dalam penyusunan klausula. Sementara itu, perlindungan data pribadi meskipun telah memperoleh landasan normatif, belum efektif karena lemahnya pengawasan dan mekanisme pemulihan. Oleh karena itu, diperlukan reformulasi kontrak digital yang mengintegrasikan transparansi, proporsionalitas risiko, dan kontrol pengguna atas data guna mewujudkan ekosistem P2PL yang adil dan beretika. Kata kunci: fintech; keadilan kontraktual; data pribadi; P2PL; kontrak digital.